Implementation of the Sociodrama Project in British Parliamentary Debate to Develop Students Political Literacy - Edi Kusnadi; Muhammad Fathurozi Chan; Nova Ra Permanata; Resti Restiah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
In the context of strengthening civic education, political literacy is an essential competency that must be instilled early on to students. Political literacy includes an understanding of rights and obligations as a citizen and awareness of socio-political dynamics. In addition to knowledge of the political system, political literacy also involves the ability to think critically, argue, and actively participate in democratic life. This study aims to determine the level of political literacy of students in class X SMAN 21 Bandung, the implementation of the British Parliamentary Debate (BPD) Sociodrama project in learning Pancasila and Citizenship Education, and the relevance of the method in developing political literacy. The method used is descriptive qualitative, describing phenomena in a natural context. The results showed that the learners political literacy level was in the positive developing category, with an understanding of basic political concepts and active participation in discussions. The implementation of the BPD Sociodrama project proved effective in training critical thinking skills, teamwork, argumentative skills, and emotional control. This approach is very relevant in developing political literacy in an integrated manner in the cognitive, affective, and psychomotor domains. The findings highlight that the integration of British Parliamentary Debate and sociodrama serves not only as an effective pedagogical strategy but also as a transformative approach that enhances students critical engagement and democratic awareness, thereby contributing significantly to the improvement of political literacy learning quality in civic education.